The effect of net foreign transactions and foreign ownership on the price of PT Gudang Garam Tbk stock - Damai Emanuel; Anton Wachidin Widjaja (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
PT Gudang Garam Tbk (GGRM) is a major cigarette manufacturer in Indonesia. GGRM was listed on the Jakarta and Surabaya Stock Exchanges on August 27, 1990. GGRM has shown resilience throughout the crisis (pandemic covid-19) and delivered positive earnings, but its price has continued to fall from July 2018 to August 2021. During the same period, foreign ownership of GGRM decreased. The decline in foreign ownership was followed by a decline in GGRM's price. The decrease in foreign ownership was the impact of the net foreign sell of GGRM. This study explores the impacts of foreign ownership and net foreign transactions on the price of GGRM and the significance of the two variables on the GGRM price. The study used secondary data available at www.IDX.co.id and www.ksei.co.id for the years 2018-2021. The multiple linear regression method was used to analyze the data. SPSS version 25 was utilized for data processing. The analysis showed that foreign ownership and net foreign transactions had a positive effect on the price of GGRM. However, only foreign ownership affects the price of GGRM stock significantly.